The law-growth nexus : the rule of law and economic development - Dam, Kenneth W. (Washington, D.C. : Brookings Institution Press, 2006)
'Examines the underlying mechanisms through which the law, judiciary, and legal profession influence the economy. Analyzes enforcement, contracts, and property rights--the concepts collectively defining rule of law--and examines their roles in the real estate and financial sectors. Extended China analysis assesses the importance of the rule of law'--Provided by publisher.
Why this book? -- Part I : Perspectives on law and economic development. 1. Where does the rule of law fit in economic development? 2. Legal institutions, legal origins, and governance. 3. Competing explanations. 4. Institutions and history -- Part II : Enforcement, contracts, and property. 5. Judiciary. 6. Contracts and property. 7. Land -- Part III : The financial sector. 8. Equity markets and the corporation. 9. Credit markets, banks, and bankruptcy -- Part IV : A review of some key themes. 10. The implications of a rule-of-law approach to economic development. 11. China as a test case.
Includes bibliographical references (p. 279-311) and index.
Keywords: Economic development; Rule of law